Cost-effectiveness analysis of durvalumab plus chemotherapy as first-line treatment for biliary tract cancer - Ye, Zhuo-miao; Xu, Zhe; Li, Huan; Li, Qian (Frontiers in Public Health, 2023)
Objective The TOPAZ-1 trial reported a significant survival benefit of durvalumab in combination with chemotherapy for the first-line treatment of biliary tract cancer (BTC). However, no studies have evaluated the economics of this treatment option. The aim of this study was to assess the cost effectiveness of durvalumab plus chemotherapy compared to placebo plus chemotherapy from the perspective of US and Chinese payers. Methods Based on clinical data from the TOPAZ-1 trial, a Markov model was developed to simulate 10-year life expectancy and total healthcare costs for patients with BTC. The treatment group received durvalumab in combination with chemotherapy and the control group received placebo plus chemotherapy. The primary outcomes analyzed included quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs). Uncertainty in the analysis results was assessed by sensitivity analysis. Results For US payers, the placebo plus chemotherapy group had a total cost of 56,157.05 and a utility of 1.10 QALYs, while the durvalumab plus chemotherapy group had a total cost of 217,069.25, a utility of 1.52 QALYs, resulting in an ICER of 381,864.39/QALY. For Chinese payers, the ICER of durvalumab plus chemotherapy group was 367,608.51/QALY. Sensitivity analysis showed that the analysis was most sensitive to the price of durvalumab. For US and Chinese payers, under the respective willing to pay thresholds, the likelihood of the durvalumab plus chemotherapy arm being cost-effective was 0%. Conclusions Both in China and in the US, durvalumab in combination with chemotherapy is not a cost-effective option for the first-line treatment of BTC compared with chemotherapy.